Agrobacterium tumefaciens divisome proteins regulate the transition from polar growth to cell division. Issue 4 (4th March 2019) - Howell, Matthew; Aliashkevich, Alena; Sundararajan, Kousik; Daniel, Jeremy J.; Lariviere, Patrick J.; Goley, Erin D.; Cava, Felipe; Brown, Pamela J.B.
Summary: The mechanisms that restrict peptidoglycan biosynthesis to the pole during elongation and re‐direct peptidoglycan biosynthesis to mid‐cell during cell division in polar‐growing Alphaproteobacteria are largely unknown. Here, we explore the role of early division proteins of Agrobacterium tumefaciens including three FtsZ homologs, FtsA and FtsW in the transition from polar growth to mid‐cell growth and ultimately cell division. Although two of the three FtsZ homologs localize to mid‐cell, exhibit GTPase activity and form co‐polymers, only one, FtsZAT, is required for cell division. We find that FtsZAT is required not only for constriction and cell separation, but also for initiation of peptidoglycan synthesis at mid‐cell and cessation of polar peptidoglycan biosynthesis. Depletion of FtsZAT in A. tumefaciens causes a striking phenotype: cells are extensively branched and accumulate growth active poles through tip splitting events. When cell division is blocked at a later stage by depletion of FtsA or FtsW, polar growth is terminated and ectopic growth poles emerge from mid‐cell. Overall, this work suggests that A. tumefaciens FtsZ makes distinct contributions to the regulation of polar growth and cell division. Abstract : In Agrobacterium tumefaciens, unipolar elongation is followed by growth at mid‐cell, enabling cell division. Remarkably, the absence of FtsZAT causes growth poles to accumulate due to tip splitting events because peptidoglycan synthesis is not redirected from the growth pole to mid‐cell. In contrast, the absence of downstream division proteins, FtsA or FtsW, causes ectopic growth poles to emerge from mid‐cell, indicating that these proteins are not necessary for the redirection of growth to mid‐cell.